Effects of Surgically Implanted Acoustic Tags on Body Condition, Growth, and Survival in a Small, Laterally Compressed Forage Fish. Issue 4 (14th June 2018) - Klinard, Natalie V.; Halfyard, Edmund A.; Fisk, Aaron T.; Stewart, Thomas J.; Johnson, Timothy B.
Abstract: Telemetry studies often assume a lack of adverse effects caused by tag attachment and presence in various species and size‐classes, which may lead to inaccurate conclusions about fish behavior in field studies. Studies that examine the effects of tagging are typically performed on salmonids and adult fishes rather than on the small fishes that are increasingly becoming the focus of telemetry studies. The objectives of this study were to assess the effects of intracoelomic acoustic tagging on growth, condition, survival, and tag retention in subadult hatchery Bloaters Coregonus hoyi (a focal species for restoration efforts in the Laurentian Great Lakes) and to determine the maximum tag burden below which tag effects are reduced. Fish were either tagged with one of three dummy acoustic transmitters (Vemco V6: n  = 50; V7: n  = 50; V9: n  = 50) or were followed as controls ( n  = 50; anesthesia, PIT‐tagging, and handling only) or sham individuals ( n  = 49; anesthesia, surgery, suturing, and PIT‐tagging but no acoustic tag implanted). Tags represented 1.3–9.0% of body mass. All fish received a PIT tag for individual identification throughout the 6‐month monitoring period (November 2014–May 2015). Survival exceeded 90% in all treatment groups, and the tag retention rate was 100%. All surviving fish appeared healthy and in excellent condition at the conclusion of the experiment. The results of this study suggest that acoustic transmitters with a tag mass : body mass ratio of 9% or less can be successfully implanted intracoelomically into subadult Bloaters—small, laterally compressed pelagic fish—with no adverse effects.